What Happens When Employers Can No Longer Discriminate in Job Ads? - Kuhn, Peter; Shen, Kailing (American Economic Review, 2023)
When employers' explicit gender requests were unexpectedly removed from a Chinese job board overnight, pools of successful applicants became more integrated: women's (men's) share of callbacks to jobs that had requested men (women) rose by 61 (146) percent. The removal “worked” in this sense because it generated a large increase in gender-mismatched applications, and because those applications were treated surprisingly well by employers, suggesting that employers' gender requests often represented relatively weak preferences or outdated stereotypes. The job titles that were integrated by the ban, however, were not the most gendered ones, and were disproportionately lower-wage jobs. (JEL J16, J23, J41, J63, J71, M51, P31)